2019
DOI: 10.3390/membranes9120161
|View full text |Cite
|
Sign up to set email alerts
|

Reference Electrodes with Polymer-Based Membranes—Comprehensive Performance Characteristics

Abstract: Several types of liquid membrane and solid-state reference electrodes based on different plastics were fabricated. In the membranes studied, equitransferent organic (QB) and inorganic salts (KCl) are dispersed in polyvinyl chloride (PVC), polyurethane (PU), urea-formaldehyde resin (UF), polyvinyl acetate (PVA), as well as remelted KCl in order to show the matrix impact on the reference membranes’ behavior. The comparison of potentiometic performance was made using specially designed standardized testing protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 78 publications
0
24
0
Order By: Relevance
“…(2) In addition to the WE of SC-ISEs, the RE should be given more attention. Currently, polymer-based [92][93][94], ionic liquid-junction [95][96][97], and lipophilic salts modified-polymer [98,99] are the main solid-state REs. Recently, a solid-state RE of Ag/AgI based on a self-referencing pulstrode offers a new strategy [100].…”
Section: Discussionmentioning
confidence: 99%
“…(2) In addition to the WE of SC-ISEs, the RE should be given more attention. Currently, polymer-based [92][93][94], ionic liquid-junction [95][96][97], and lipophilic salts modified-polymer [98,99] are the main solid-state REs. Recently, a solid-state RE of Ag/AgI based on a self-referencing pulstrode offers a new strategy [100].…”
Section: Discussionmentioning
confidence: 99%
“…The potentiometric measurements were performed using a homemade 16-channel set-up. The input impedance was greater than 10 13 Ohms, and the input current was lower than 20 fA for each of the 16 inputs and the reference electrode input. The multi-channel potential-meter was coupled with a personal computer equipped with a 16-bit resolution data acquisition card PCI DAS 6014 (Computer Boards; Norton, MA, USA) or a 16-bit resolution data acquisition card USB1606G (MC Measurements Computing, Norton, MA, USA) and custom-made software.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Indeed, the materials used and the fabrication technology, the methods of characterization and testing have been, and are, distinctly different, see: [ 7 ]. However, new expectations and a need for ion-monitoring have inspired a boom of interest in designing reference electrodes, which is reflected in numerous reports [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the very empirical report on plastic membranes with dispersed equitransferent electrolytes, Lingenfelter and co-authors [ 12 ] showed how to obtain the reference electrodes. The research in this area is governed by the idea that there is a wide insensitivity towards ions in the matrices, which is opposite to the aim of ion sensors.…”
mentioning
confidence: 99%